Women and the Incarceration Epidemic: What Every Healthcare Provider Needs to Know - The Case of Nicole Anderson - Candace Robertson-James; Ana Núñez; Allison Myers (Association of American Medical Colleges, 2011)
Abstract Introduction Due to the increasing numbers of women who are incarcerated, as well as the relatively short sentences that are served, there are growing numbers of women in the community with a history of incarceration. Moreover, these women often have unique health needs. This is a curricular case that teaches critical knowledge, attitudes and skills necessary for treating women with a history of incarceration. The goal of this case is to increase student awareness of the incarceration epidemic among women and implications for health care providers. Methods This module is designed to be administered to small groups of preclinical students over two sessions. The first session includes an introduction to and review of the Ms. Anderson case and identification of key learning issues students will experience as they progress through the case. The second session includes a robust discussion of some of the key points of Ms. Anderson's story as they relate to all of the learning issues presented and resources provided in the case. Throughout the experience, students are introduced to key concepts related to social determinants of health specific to incarceration. Students will discuss the prevalence rates and reasons for incarceration among women offenders, demographic characteristics, health risks and issues commonly experienced, barriers to care, screening protocols, reasons for noncompliance in patients, and how to effectively include questions about incarceration status in to the social history. Results First- and second-year medical students at Drexel University College of Medicine (DUCOM) participated in a curricular pilot on the developed curriculum. Overall, students stated that they did not feel prepared to address the healthcare needs of women with a history of incarceration. All of the students stated that the DUCOM curriculum has "never addressed" or "rarely addressed" issues of patients with a history of incarceration and health care. Most students (89%) stated they have never included questions about a history of incarceration in their social history. All of the students agreed this case-based curriculum provided useful information and it enhanced their knowledge related to incarceration and the health of female patients. In addition, 88% agreed that the curriculum helped them to better address the needs of a female patient with a history of incarceration and utilize pertinent screening protocols. Pre-/posttest score results showed an increase in interest in working with offender and ex-offender populations as well as an increase in students' ability to identify barriers to effective healthcare for women with a history of incarceration. Discussion This case successfully increased student awareness of the incarceration epidemic among women and implications for health care providers. This case was supported by a grant from the Valentine Foundation.